2018
DOI: 10.1038/s41467-018-03770-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of NAT10 enhances healthspan in a mouse model of human accelerated aging syndrome

Abstract: Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare, but devastating genetic disease characterized by segmental premature aging, with cardiovascular disease being the main cause of death. Cells from HGPS patients accumulate progerin, a permanently farnesylated, toxic form of Lamin A, disrupting the nuclear shape and chromatin organization, leading to DNA-damage accumulation and senescence. Therapeutic approaches targeting farnesylation or aiming to reduce progerin levels have provided only partial health imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 53 publications
5
96
0
Order By: Relevance
“…In addition, changes in the localization and regulation of Cx43 and gap junctions has been described in many forms of cardiac diseases and contribute to the arrhythmogenic substrate (44)(45)(46)(47)(48). (58,59). These data suggest a role of A-type lamins in the regulation of acetylation.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, changes in the localization and regulation of Cx43 and gap junctions has been described in many forms of cardiac diseases and contribute to the arrhythmogenic substrate (44)(45)(46)(47)(48). (58,59). These data suggest a role of A-type lamins in the regulation of acetylation.…”
Section: Discussionmentioning
confidence: 86%
“…One of the most striking compounds has been remodelin, which improves nuclear architecture, chromatin organization, and fitness of progerin-expressing cells, without significantly impacting progerin production [106]. Targeting NAT10, the target of remodelin, also significantly increase lifespan in a mouse model of disease [83]. Other novel therapies, like in vivo partial reprogramming, also improved the phenotype [82].…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…While these data address how lower NAT10 expression affects HIV-1 replication, it is also possible to inhibit NAT10 function in WT cells using a drug, called Remodelin, that has been reported to inhibit NAT10 function at concentrations that are non-toxic in culture or in mice 13,14 . Indeed, we observed that Remodelin reduced HIV-1 replication in WT CEM cells by up to 70%, but had little effect on HIV-1 replication in the ΔNAT10 CEM cells, at concentrations that did not reduce CEM cell growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, reduced expression of NAT10, and the concomitant decrease in the level of ac4C on viral RNAs, inhibits HIV-1 replication by reducing HIV-1 RNA stability. Interestingly Remodelin, a previously reported inhibitor of NAT10 function 13,14 , also inhibits HIV-1 replication without affecting cell viability, thus raising the possibility that the addition of ac4C to viral mRNAs might emerge as a novel cellular target for antiviral drug development.…”
mentioning
confidence: 99%